Activity-based costing technology adoption in Australian universities - Abeysekera, Indra; Sharma, Rajeev (Frontiers in Psychology, 2023)
Strategic cost management is vital to the Australian university sector performance, and Activity-Based Costing (ABC) is a widely accepted and used accounting technology assisting in that direction. This study examines the status of ABC technology adoption in two categories: adopters and non-adopters, informed by Social Cognitive Theory and Dynamic Theory of Strategy. The study collected data by sending a pilot-tested survey questionnaire to complete electronically by senior executives. Of the 39 universities that elected to participate, it received 24 usable responses, representing a 61% response rate. The data analyzed using descriptive analysis described adopter characteristics, adoption continuity, and institutional features of Universities ABC technology adopter and non-adopter status. The descriptive analysis led to identifying five contextual determinant variables. Revenue, staff size, city-based versus regional, southern Australian location versus other, and university prestige were determinants tested for ABC technology adoption using binary logistic regression. All determinants were significant except for the University's prestige status. The odds ratios revealed that revenue had the most influence, followed by geographic location as a city-based or regional University.